Pleiotropic Multifaceted Therapeutic Potential of Phyllanthus amarus - Rohilla, Ankur (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Herbal drugs constitute a major share of all the officially recognized systems for the treatment of a wide range of diseases. More than 70% of world’s population still uses the non-allopathic systems of medicine. Indian medicinal plants provide a rich source for health care moieties to prevent different diseased states. In spite of the great progress observed in modern medicinal systems in recent decades, herbal drugs still make an important involvement to health care. Phyllanthus amarus, a distinguished botanical worldwide, has been used since many years because of its rich medicinal importance. Phyllanthus amarus is a small, erect, annual herb having large number of phytochemicals that are attributed to its leaves, stem and roots. A wide array of studies anti-inflammatory, antidiabetic, antimicrobial, antihyperlipidemic, antioxidant, anticancer, hepatoprotective, antifertility, antidiarrhoeal, antiallodynic, antioedematogenic, antispasmodial, chemoprotective, antihypercalciuric, antiviral, antispasmodic, antinociceptive and diuretic properties associated with Phyllanthus amarus. The present review article summarizes about the phytochemicals associated with the plant. Moreover, numerous pleiotropic properties exhibited by the plant are also clearly discussed.